1999
DOI: 10.1111/j.1532-5415.1999.tb07235.x
|View full text |Cite
|
Sign up to set email alerts
|

The Nursing Home at Night: Effects of an Intervention on Noise, Light, and Sleep

Abstract: The significant reductions in noise and light events resulting from the intervention did not lead to significant improvements in the day sleep and most night sleep measures. An intervention that combines both behavioral and environmental strategies and that addresses daytime behavioral factors associated with poor sleep (e.g., excessive time in bed) would potentially be more effective in improving the night sleep and quality of life of nursing home residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
116
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 17 publications
2
116
0
Order By: Relevance
“…The empirical evidence of the negative impact on sleep in shared rooms in hospitals is fairly strong (Duffin, 2002;Ulrich & Zimring, 2004), although in nursing homes the evidence is weaker (Schnelle, Alessi, Al-Samarrai, Fricker, & Ouslander, 1999).…”
Section: Results Of the Literature Reviewmentioning
confidence: 99%
“…The empirical evidence of the negative impact on sleep in shared rooms in hospitals is fairly strong (Duffin, 2002;Ulrich & Zimring, 2004), although in nursing homes the evidence is weaker (Schnelle, Alessi, Al-Samarrai, Fricker, & Ouslander, 1999).…”
Section: Results Of the Literature Reviewmentioning
confidence: 99%
“…These studies have shown that it is extremely difficult to change the long-term care environment, and despite considerable efforts by researchers, the environment remains quite noisy at night. 35,37,38 An alternative approach is to use multi-component interventions to address both internal physiological causes of sleep disturbance and external environmental factors. One such study tested a short-term (5-day) intervention combining daytime light exposure and physical activity, a structured and regularly-timed bedtime routine, reduced time in bed during the day plus provision of nighttime nursing care in a manner that minimizes disruption to sleep.…”
Section: Non-pharmacological Treatment Of Sleep Problemsmentioning
confidence: 99%
“…The effect that increased noise has on patients has been evaluated in a variety of hospital settings, most notably in pediatric and adult intensive care units and nursing homes. 9,10 Noise has been shown to increase blood pressure, heart rate, respiratory rate, and body temperature. It has also been associated with failure to thrive, impaired immune function, delayed wound healing, and increased stress levels.…”
mentioning
confidence: 99%